High serum levels of CA 19-9 and CYFRA21-1 caused by renal pelvis urothelial carcinoma: a report of two cases. Issue 3 (March 2021) - Yin, Guolin; Zhang, Miaomiao; Zhao, Bing; Yang, Zaixing
Carbohydrate antigen 19-9 (CA19-9) and cytokeratin 19 fragment (CYFRA21-1) are widely used as tumor markers in clinical practice and are increased in many neoplasms. However, although increased serum CA19-9 levels have been found in some Japanese patients with renal urothelial carcinoma (UC), they have not been detected in patients from other countries or regions, and increased serum CYFRA21-1 levels haves not been reported in patients with renal UC. We analyzed serum CA19-9 and CYFRA21-1 levels in two patients with renal UC and monitored the changes in levels during postoperative follow-up. Both cases with renal pelvis UC had high levels of serum CA19-9 and CYFRA21-1, which decreased to within normal ranges after successful surgery, suggesting a causal relationship between renal UC and increased serum CA19-9 and CYFRA21-1. Because serum levels of CA19-9 and CYFRA21-1 are increased in many neoplastic diseases, they may not be reliable tumor markers for the screening and diagnosis of renal UC. However, they may be useful noninvasive indicators for assessing treatment effects in patients with renal pelvis UC with elevated pretreatment serum CA19-9 or CYFRA21-1.